Identifikasi Senyawa Antikanker dari Fraksi Kloroform Kulit Batang Bruguiera gymnorhiza dan Aktivitas Sitotoksiknya - Warsinah, .; Sismindari, .; Susidarti, Ratna Asmah (Indonesian Research Gateway)
Bruguiera gmnorhiza is one of mangrove plant that has not been widely studied as potential anticancer compounds. Previous research noted that the methanol extract of the bark of B.gymnorhiza are cytotoxic towards HeLa cells. The purpose of this study was to determine the compounds in the chloroform fraction and cytotoxic activity in HeLa cells. Stem bark of B. gumnorhiza was extracted with methanol, further fractionation by partitioning method, using of the solvent h-hexane and chloroform. Fraction of chloroform was evaporated, the tested cytotoxic activity against HeLa cells by MTT method and apoptotic induction by double staining method. Faction levels are used for 500, 250, 125, 62.5 and 31.25 mg/mL with 24-hour incubation time. Subsequent fractions were identified by GC-MS method. The result showed that the chloroform fraction contains 21 compounds, 6 in the form of fatty acids and terpenoids that have anticancer cytotoxic activity (IC50) of 134 ug/mL with apoptotic mekanism.Keywords: Apoptosis, Bruguiera gymnorhiza, cytotoxic, Fractionation, HeLa cell